Accommodating multiple interests in local forest management - Wollenberg, Eva Karoline; Edmunds, D.; Anderson, J. (2001)
This special issue contains an editorial and seven articles. They examine the emerging pluralism in the governance of forests. Forests are naturally suited to pluralistic decision-making because of the many products and services they provide. They often involve complex arrangements for accommodating multiple interests, especially through local common property institutions. Yet, conflict persists among these diverse uses and users and has become more visible of late with the stronger voices of NGOs and community-based organizations. The papers suggest future direction for the improvement of accommodation on local forest management.